Gambaran Histopatologi Pankreas Tikus Putih (Rattus norvegicus) Pasca Perlakuan Iskemia-Reperfusi Ginjal - Elva Rosiana; Wiwit Ade Fidiawati; Darmawi Darmawi (Jurnal Ilmu Kedokteran, 2019)
Ischemic-reperfusion injury is defined by a condition of hypoperfusion in the spesific organ followed by reperfusion (reoxygenation) inducing tissue damage. Tissue damage produces reactive oxygen species (ROS) leading to oxidative stress condition. Oxidative stress mediate the lipid peroxidation reactions, harm the cell and finally facilitate the cell death. The aim of this study was to evaluate the histopathologic feature of white rat’s pancreas post renal ischemiareperfusion. This study was an experimental laboratory research with post-test-only control group design including 20 male white rats. Rats were divided into 5 groups, control, treatment 1 (45 minutes ischemia), treatment 2 (45 minutes ischemia followed by 1 hour reperfusion), treatment 3 (45 minutes ischemia followed by 2 hours reperfusion) and treatment 4 (45 minutes ischemia followed by24 hours reperfusion). We found the change of the histopathological characteristics of white rat’s pancreas in term of edema, leukocyte infiltration and vacuolization.